Primary biliary cirrhosis and hepatic sarcoidosis – A case report - Alempijević, Tamara; Sokic-Milutinović, Aleksandra; Tončev, Ljubiša; Pavlović-Marković, Aleksandra; Djuranovic, Srdjan; Tomanović, Nada; Drulović, Jelena (Vojnosanitetski pregled, 2013)
Introduction. Primary biliary cirrhosis (PBC) is an immune-mediated chronic progressive inflammatory liver disease leading to destruction of small interlobular bile ducts. Sarcoidosis is a chronic disorder of unknown etiology characterized by non-caseous granulomas. Case report. We reported a 69-year-old female patient with abdominal pain, malaise, vertigo, headaches, hands tremor and partial loss of hearing. Initial laboratory findings revealed elevated liver function tests and cholesterol with positive antimytochondrial and antinuclear antibodies. Liver biopsy revealed granuloma typical for PBC and granulomatous lesions typical for sarcoidosis. Elevated serum angiotensin-converting enzyme and granulomatous lesion on the brain magnetic resonance imaging (MRI) were detected and the patient was diagnosed with overlap of PBC and liver sarcoidosis and neurosarcoidosis. The patient was treated with ursodeoxicholic acid (UDCA) and prednisolone. Six months later the patient was symptom-free with laboratory findings within normal range. Conclusion. In PBC patients it is important to consider coexisting granulomatous liver diseases if elevated liver function tests persist despite UDCA therapy.
Keywords: liver cirrhosis; biliary; sarcoidosis; diagnosis; differential; histological techniques; treatment outcome